American way of drawing: American manuals in the design of the military bases in Spain - Salazar, María del Pilar (Cuadernos de Proyectos Arquitectónicos, 2018)
Abstract In the elaboration of the plans for the military bases, built by Americans and Spaniards in Spain in the 50s, the American military design manuals were used. That was one of the first times the Spanish architects drew plans from constructive catalogues. The architectural firms, the engineering companies and the construction companies adapted this way of working, considerably different from what they were used to do and they learnt the American way of representation. The American plans had a high level of precision, they used their own codes, complicated verification systems, their own symbols, lines and materials and they had the additional difficulty that every text should be both in English and Spanish. This article offers some objective references about a change of methodology process, trying to contribute to the analysis of the relation between the existing architecture and the method it was represented. At the same time, we try to show the repercussions that the work of the Spanish architectural firms together with the Americans had in their change of methodology, especially in the graphic representation of the plans.